A re-examination of the whiplash associated disorders (WAD) as a systemic illness. Issue 9 (24th February 2005) - Ferrari, R; Russell, A S; Carroll, L J; Cassidy, J D
Abstract : Objective: To describe the systemic nature of the illness reported after motor vehicle collisions using data from a large, population based cohort of individuals making an injury insurance claim. Methods: All subjects who submitted a claim or were treated for whiplash injury following a motor vehicle collision in Saskatchewan, Canada during an 18 month period were examined. Demographics of claimants, collision related data, pre-collision health data, symptom prevalence, and scores on the short form 36 item general health survey (SF-36) were obtained on average within one month post-collision. Results: Of 9006 potentially eligible claimants, 7462 (83%) met criteria for whiplash injury and provided information regarding demographics and injury related symptoms; 45% of these consented to complete the SF-36 at baseline. For most subjects, neck pain was only one of many diffuse and intense symptoms, including, often, low back pain. The range of symptoms, including fatigue, dizziness, paraesthesiae, headache, spinal pain, nausea, and jaw pain, could be interpreted as a systemic disorder. SF-36 scores showed low physical and mental functioning one month post-collision. Conclusions: What is commonly referred to as whiplash associated disorders (WAD) is best appreciated as a syndrome extending well beyond what can be labelled as a neck injury. More research is needed for a better understanding of the underlying mechanisms involved so that treatment can be directed at the broad spectrum of the illness rather than focusing on finding a focal neck injury.